Modeling population dynamics and economic growth as competing species: An application to CO2 global emission - Salvador Enrique Puliafito; José Luis Puliafito; Mariana Conte Grand (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2006)
Since the beginning of the last century the world is experiencing an important demographic transition, which will probably impact on economic growth. Many demographers and social scientists are trying to understand the key drivers of such transition as well as its profound implications. A correct understanding will help to predict other important trends of the world primary energy demand and the carbon emission to the atmosphere, which may be leading to an important climate change. This paper proposes a set of coupled differential equations to describe the changes of population, gross domestic product, primary energy consumption and carbon emissions, modeled as competing-species as in Lokta-Volterra prey-predator relations. The predator–prey model is well known in the biological, ecological and environmental literature and has also been applied successfully in other fields. This model proposes a new and simple conceptual explanation of the interactions and feedbacks among the principal driving forces leading to the present transition. The estimated results for the temporal evolution of world population, gross domestic product, primary energy consumption and carbon emissions are calculated from year 1850 to year 2150. The calculated scenarios are in good agreement with common world data and projections for the next 100 years.
Keywords: 330; population dynamics; economic growth; primary energy consumption; carbon emission model; Lokta-Volterra Equations; prey-predator model; Bevölkerungswachstum; Sozialprodukt; Energiekonsum; Treibhausgas-Emissionen; Theorie